The Effects of One-Stage Full-Mouth Disinfection and Qua-drant-Wise Scaling and Root Planing on Serum Levels of IL-17 and IL-1β and Clinical Parameters (A randomized Controlled Trial Study). - Adileh Shirmohammadi; Zohreh Babaloo; Amir Eskandari; Reza Purabbas; Amirreza Babaloo (Tehran University of Medical Sciences, 2013)
One-stage full-mouth disinfection technique (FMD) has been introduced to avoid cross-contamination between the treated and untreated regions between treatment sessions. Considering the role of inflammatory mediators in periodontitis, the aim of the present study was to compare the effects of FMD with the quadrant-wise scaling and root planing (Q-SRP) on serum levels of IL-17 and IL-1β in patients with moderate-to-severe chronic periodontitis.Twenty patients with chronic periodontitis were selected randomly and based on inclusion criteria in each group. In order to evaluate the periodontal status, the clinical parameters of bleeding on probing (BOP), clinical attachment level (CAL), probing depth (PD) and modified gingival index (MGI) were measured and recorded before treatment and at 2- and 4-month intervals after treatment. Immunologic parameters of the study such as IL-17 and IL-1β serum levels were determined by special laboratory kits at the same intervals. Data were analyzed by SPSS 15 statistical software. Statistical significance was defined at p0.05). In the evaluation of periodontal parameters, all parameters exhibited clinical improvements in both groups, with no statistically significant differences between the two study groups (p>0.05).Based on the results of the present study it was concluded that both FMD and Q-SRP techniques result in improvements in periodontal indexes and decreases in the serum levels of IL-17 and IL-1β inflammatory mediators.